2006
DOI: 10.1038/sj.bjp.0706794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginseng saponins isolated from Red Ginseng roots on burn wound healing in mice

Abstract: We recently demonstrated that ginsenoside Rb1 (C54H92O23, molecular weight 1108) isolated from ginseng, when intravenously infused into rats with permanent middle cerebral artery occlusion, reduced cerebral infarct volume and ameliorated place navigation disability of the animals, through an anti‐apoptotic action and possibly promotion of vascular regeneration. To investigate the ginsenoside Rb1‐mediated vascular regeneration in vivo in a more easily accessible experimental systems, we made a burn wound on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 38 publications
1
89
0
3
Order By: Relevance
“…ginseng has been shown to possess a wide range of biological and pharmacological activities and is used as a general tonic in traditional oriental medicine to increase vitality, health, and longevity, especially in older persons. Previous research has reported that ginseng has several beneficial effects on human and animal skin [3][4][5][6][7]. Kim et al [36] reported that topical applications of total ginseng saponins (10 pg or 100 ng/mouse) and ginsenoside Rb1 (100 fg, 10 pg, or 1 ng/mouse) isolated from red ginseng significantly inhibited increases in skin thickness and wrinkle formation and reduced skin elasticity induced by long-term UVB irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…ginseng has been shown to possess a wide range of biological and pharmacological activities and is used as a general tonic in traditional oriental medicine to increase vitality, health, and longevity, especially in older persons. Previous research has reported that ginseng has several beneficial effects on human and animal skin [3][4][5][6][7]. Kim et al [36] reported that topical applications of total ginseng saponins (10 pg or 100 ng/mouse) and ginsenoside Rb1 (100 fg, 10 pg, or 1 ng/mouse) isolated from red ginseng significantly inhibited increases in skin thickness and wrinkle formation and reduced skin elasticity induced by long-term UVB irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several works using aluminum coupled to the soldering iron have been presented as an effective method for the reproduction of the experimental model of third degree burns 8,9,[16][17][18][19] , but there is a great discrepancy in the temperature used, which may vary from 100ºC to 200ºC, in addition to the time of application that varies between 5 to 30 seconds. Caliari-Oliveira et al…”
Section: ■ Discussionmentioning
confidence: 99%
“…Subsequently, the process of burning the skin of the animal was started through a 3 cm diameter circular aluminum plate coupled to a soldering iron, with a total weight of 190 grams [8][9][10] (Figure 1), heated at a temperature of 150 °C, controlled with the aid of a thermostat ( Figure 2) [10][11][12] . The plate was pressed in the dorsal region of the animals in three different times, being for G5: 5 seconds, G10: 10 seconds and G15: 15 seconds.…”
Section: Experimental Model Of Third-degree Burnmentioning
confidence: 99%
“…Hamed Jafari Vayghan 1 , Sevda Saleh Ghadimi 1 , Ali Reza Nourazarian 2,3 * (Yue et al, 2006) 4-reduce inflammatory responses, (Oh GS et al, 2004;Kimura et al, 2006) According to previous studies ginseng can be beneficial in the treatment and prevention of colorectal cancer (Yun and Choi 1995;Yun et al, 2001;Yun 2003a). The aim of this study was to review relevant literature on ginseng effects on colorectal cancer.…”
Section: Preventive and Therapeutic Roles Of Ginseng -Focus On Colon mentioning
confidence: 99%